Studi Komparasi Kitab Tadhkirotu Alsa ̅mi’ Walmutakallim Fi ̅l A ̅lda ̅b Al’a ̅lim Wa Almuta’allim dan A ̅da ̅bu Al’a ̅lim Wa Almuta’allim Tentang Manajemen Pendidikan - Tunnisa, Faiza; Mujahada, Kharis Syuhud (Yayasan Rahmat Islamiyah, 2024)
This research aims to find the perspective and approach of both books to character education management. This research uses a qualitative approach and the type of study used is the literature review. The main source of data for this research is both this book itself, and previous research or literary study. The results of this research show that in the Book of Tadzkirah as-Sami’ wa al-Mutakkallim Fi Adab al-’Alim Wa al-Muta’alim, Imam Ibnu Jama'ah uses an approach that focuses on application in the environment and character education, in accordance with the custom of Salaf scholars. There are three chapters in this book concerning disciples: disciples against teachers, disciples in the congregation, and disciples themselves. On the other hand, the book of Kh. Hasyim Asy'ari, that is, the Book of Adabul Alim wal Muta’allim only deals with character education in one chapter, namely the attitude of pupils to teachers, and the implementation of character education that emphasizes more ethics and is adapted to the character of today’s Indonesian children. Important research, conclusions, and implications of research results.